Proceedings of the 2009 International Cross-Disciplinary Conference on Web Accessibililty (W4A) 2009
DOI: 10.1145/1535654.1535683
|View full text |Cite
|
Sign up to set email alerts
|

User requirement analysis for a railway ticketing portal with emphasis on semantic accessibility for older users

Abstract: In this paper, we present the results from a survey on user requirements for older users of online ticketing services of a nationwide railway ticket and travel information portal. Our survey shows that older users differentiate in their attitude towards internet according to their experience with internet services and the service provided, not only according to their age. Further, our study indicates that in contrary to common belief advertisement or interactive elements are not perceived as negative all the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In this study, participants discussed a variety of ecological and societal barriers to activities that have been largely [45,54,56], economic opportunities enabled by emerging technologies [9], and platforms that challenge stigma [43].…”
Section: Expanding Past Individual Responsibilitymentioning
confidence: 99%
“…In this study, participants discussed a variety of ecological and societal barriers to activities that have been largely [45,54,56], economic opportunities enabled by emerging technologies [9], and platforms that challenge stigma [43].…”
Section: Expanding Past Individual Responsibilitymentioning
confidence: 99%
“…But especially elderly people often have problems using OSN and ICT since existing user interfaces are often too complex for them and do not meet their special requirements [9,10,18,19]. Older and younger adults differ significantly in their way of solving problems on websites [20].…”
Section: Related Workmentioning
confidence: 99%
“…They concluded that older adults need more opportunities for collaborative learning with other people to learn Web navigation techniques. [9,10,11] presented observations of older adults using existing systems. Sayago and Blat [9] conducted a 3-year study of everyday interactions with the Web and reported that problems with remembering steps, with understanding Web and computer jargon, and with using the mouse are more significant than problems with perceiving visual information, with understanding icons, or with using the keyboard.…”
Section: Studies For Elderly Usersmentioning
confidence: 99%
“…Some users overreacted to certain voice messages or repeated the same error when they couldn't understand the situation. Leitner et al [11] found that older adults do not show major differences from younger people in their needs and preferences related to an online ticket service.…”
Section: Studies For Elderly Usersmentioning
confidence: 99%